SCIENTIFIC JUSTIFICATION FOR THE IMPLEMENTATION OF THE INTEGRATED MODEL OF RAPID TESTING FOR HIV-INFECTION AMONG KEY POPULATIONS OF KAZAKHSTAN - Alibayeva K.O.; Baiserkin B.S.; Saparbekov M.K. (Academic Journal of Physical and Chemical Sciences, 2020)
In the pipeline justify scientifically the approached on the integration of the primary health care and the Service for AIDS prevention and control when rendering services on rapid testing among key populations. It is noted that methodological basis for integration of the measures in case of HIV-infection with PHC was WHO / UNAIDS strategy "90-90-90", in which it is stated that for effective reaction to and prevention of the spread of HIV infection among key populations, it is recommended to implement an integrated set of measures including diagnosis, treatment and care connected with HIV-infection. It is noted that the integration of primary health care among key populations is carried out within the scope of the statutory free medical assistance (SFMA) and the compulsory health insurance system (CHIS). Rapid testing, pre-and post-test consulting for HIV infection, hepatitis, and STD of key populations when integrating with PHC is carried out in medical organizations, clinics, drop-in centres (DS), people-friendly offices (PFO), NGOs with the involvement of social workers and outreach workers. The integrated activities foresee social support that shall provide access both to medical and psychosocial support services for the key populations.